Margaret Hillert's: Little Puff - Hillert, Margaret; Dammer, Mike (Chicago, IL Norwood House Press, 2017)
"Tired of working alone, a little train jumps off the track in search of companionship and ends up at the zoo, where it gives rides and makes people happy"--
a"A Beginning-to-Read book."
a"21st Century Edition."
a"Authorized adapted reprint from the U.S. English language edition, entitled Little Puff"--Title page verso.
Originally published in 2009 by Norwood House Press.
Keywords: Railroad trains -- Juvenile fiction; Zoos -- Juvenile fiction